Long non-coding and endogenous retroviral RNA levels are associated with proinflammatory cytokine mRNA expression in peripheral blood cells: Implications for schizophrenia. (April 2018) - Melbourne, Jennifer K.; Chase, Kayla A.; Feiner, Benjamin; Rosen, Cherise; Sharma, Rajiv P.
Abstract: Recent research indicates that the expression of long non-coding and endogenous retroviral RNAs is coordinated with the activity of immune molecules often dysregulated in schizophrenia. We measured the expression of TMEVPG1, NRON, HERV-W env and HERV-W gag in blood cells from participants with schizophrenia and controls. We report that a) expression levels of these non-coding RNAs are correlated with proinflammatory cytokine mRNA expression in all participants, b) HERV-W transcripts are negatively correlated with atypical antipsychotic use in participants with schizophrenia, and c) that these RNAs are transcribed in response to proinflammatory stimuli in a THP-1 monocyte cell line. Highlights: Expression of lncRNAs and cytokines are correlated in human blood cells. Expression of HERV transcripts and cytokines are correlated in human blood cells. These lncRNAs/HERVs are responsive to inflammatory stimuli in a monocyte cell line.